Kurikulum K 13 Dan Efek Pergaulan Terhadap Perilaku Bulliying Siswa - Qolbiyah, Shofwatal; Agusmad, Agusmad; Rouf, Abdul (Universitas Darul Ulum, 2022)
The objectives of this study are as follows: to find out the effect of implementing the 2013 curriculum, the effect of association on bullying behavior at MAN 4 Jombang with a quantitative explanatory research approach. The population is 136 students with Proportional Random Sampling sampling obtained 100 samples from class XII A and XII B with quantitative data analysis techniques obtained there is a partial positive effect between the implementation of the 2013 curriculum on bullying behavior at MAN 4 Jombang with an explanation that the level of bullying behavior of students can be predicted from the high and low implementation of the K-13 curriculum. That there is no partially significant effect between the effects of student association on bullying behavior at MAN 4 Jombang with the explanation that the level of student bullying behavior cannot be predicted from the high and low effects of student association. That there is an effect of implementing the K-13 curriculum and student association on behavior bullying at MAN 4 Jombang with a low proportion and other variables that can explain it is possible that the main objectives of the school are less focused on character building, infrastructure that is less supportive, and environmental role models that are less supportive.